Sem, Edax and UV-visible studies on the properties of Cu2S thin films. - Kassim, Anuar; Ho, Soon Min; Lim, Kian Siang; Nagalingam, Saravanan (2011)

(untitled)
Cu2S thin films were produced by simple chemical bath deposition technique at various bath temperatures ranging from 55 °C to 75 °C. For chemical bath deposited thin films, copper sulphate solution was employed as Cu2+ source while thiourea solution provided the S2- ions. The morphological, compositional and optical properties were investigated using scanning electron microscopy, energy dispersive analysis of X-ray and UV-Visible spectrophotometer, respectively. The grain size and average atomic ratio of Cu/S increased when the bath temperature was increased from 55 °C to 75 °C. The films deposited at 75 °C indicated high absorbance as compared with other bath temperatures.